ANALISIS HUKUM ISLAM TERHADAP JUAL BELI PATUNG: STUDI DI KECAMATAN TROWULAN KABUPATEN MOJOKERTO PERSPEKTIF ULAMA MOJOKERTO - Ari Mafrudi (Maliyah : Jurnal Hukum Bisnis Islam, 2017)
This paper discusses about the analysis of Islamic law on the perceptions of scholars (ulama) of Mojokerto about buying and selling statues in Trowulan Mojoketo regency. The author will describe the perceptions of Mojokerto Ulama' agains the practice of buying and selling statues in Trowulan Mojokerto regency then analyze it with Islamic law. The results of this study concluded that according to the perception of the ulama' Jurisprudence, buying and selling statues is haram. The scholars' argued that the practice of buying and selling sculpture has no benefit whatsoever to be traded, even that leads to mad}a>rah and syirk, because the object of buying and selling mostly to be made for a worship. Research in the field gets the perception of Mojokerto' Ulama about buying and selling the statue allowed to be viewed with maslahah mursalah with reason “Hajat (requirement) occupies emergency position, both of general intent (all people) or even special intent (one group or individual)" . Sale and purchase statues included in the intent level. The profession is to meet their needs and their families. Otherwise, they will fall into a dangerous state (hunger). Islam permits the profession as a sculptor for the reason hajah daruriyyah.